KRISIS EKONOMI DAN PERGESERAN PEMANFAATAN ANGKATAN KERJA PEREMPUAN: KASUS DI DKI JAKARTA - Abdur Rofi; Sukamdi Sukamdi (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
Issues on marginalization of women in labour market have always become an important discussion in developing countries. The success of economic development represented by high economic growth for some extend has even been argued as factor behind the low role of women in labour market. Does it mean that when economic growth decrease women participation in labour market will be better? In fact the economic crisis hit Indonesia since 1997, which lower the economic growth becoming minus, put women as first victim. Their role in labor market were even worsening. At least the evidence can be seen from the result of this study. Their participation in labour market is increasing, but it can not be interpreted as a better condition! maight be true that women were forced to enter labour market because of economic pressure in the household due to the crisis.